The OsGATA gene family as a promising candidate for applying the CRISPR/Cas genome editing technology to improve the nutritional and yield qualities of rice (Oryza sativa L.) - E. A. Nesterova; N. A. Shvachko (Труды по прикладной ботанике, генетике и селекции)
Molecular breeding of rice (Oryza sativa L.) for yield is of great importance for ensuring food security of the population. Living organisms manifest genetically determined responses to environmental factors, including stressors. Photosynthetic activity affects all metabolic processes in plant cells. The genes involved in photosynthesis, in their turn, are regulated by differentially expressed genes associated with circadian rhythms. Plants, as sedentary organisms, require more efficient regulation of gene expression. GATA factors are transcription factors (TFs) that affect the production of phytohormones and mediate the stress response. GATA factors are divided into four main classes (A to D), based on the difference in the structure of the zinc finger domain, and into seven subfamilies, depending on the availability of additional domains. GATA TFs incorporate domain structures that may be involved in the regulation of circadian rhythms. Effects on the circadian rhythms influence other regulatory metabolic pathways in plants, which makes the study of genes associated with circadian rhythms relevant and significant. The most well-known and popular method of gene editing at the moment is the CRISPR/Cas technology. More than 30 rice genes were successfully genomically edited using the CRISPR/Cas technology in the period from 2018 through 2023. This helped to improve their valuable agronomic traits.This review summarizes all information about the classification and known functions of OsGATA genes and OsGATA TFs and provides evidence for the possibility of influencing the regulation of rice photoperiodicity by editing these genes.